Perancangan Interior Pusat Hiburan Anak Berbasis Alkitab di Surabaya - Yosudhara Nariatn; Grace Mulyono (Intra, 2019)
Children nowadays are inseparable from technology in day to day basis. Their environment shapes and sharpens their social skills so they able to interact and adjust well in society in the future. Developing social skills can also be done in entertaining way as in playground or theme park. Nowadays, spiritual education is also important to introduce to children from an early age. Because technology has an important role in children’s interest, it is used in the design as a media to channel information and provide a unique experience in developing children’s spiritual faith. This design aims to create a technological forward children entertainment center with rich Christian values, so children can have fun and rejoice while learning the Holy Bible. The conclusion of this design is children can improve their social skills and introduce God’s greatness to the children through Bible stories which applied in thematic interior design.